The use of magnetic resonance imaging to predict placenta previa with placenta accreta spectrum. (23rd July 2020) - Ishibashi, Hiroki; Miyamoto, Morikazu; Shinmoto, Hiroshi; Soga, Shigeyoshi; Matsuura, Hiroko; Kakimoto, Soichiro; Iwahashi, Hideki; Sakamoto, Takahiro; Hada, Taira; Suzuki, Rie; Takano, Masashi
Abstract: Introduction: Massive hemorrhage due to placenta previa with placenta accreta spectrum is associated with high maternal mortality and morbidity. Therefore, accurate prediction of placenta previa with placenta accreta spectrum is essential; magnetic resonance imaging (MRI) is a useful tool for this purpose. This study investigated novel predictors of anterior and posterior placenta previa with placenta accreta spectrum using MRI. Material and methods: This was a retrospective study at a tertiary obstetrics hospital in Japan. The singleton patients with placenta previa who were scanned with MRI prenatally and had a cesarean section at our institution between 2007 and 2018 were included. The prediction of anterior and posterior placenta previa with placenta accreta spectrum was evaluated using four MRI findings: heterogeneous signals in the placenta, dark T2‐weighted intraplacental bands, myometrial thinning or interruption, and focal uterine bulging. The prediction of posterior placenta previa with placenta accreta spectrum was performed using the quantification of cervical varicosities, which were defined as the ratio of the distance between the minimum distance from the most dorsal cervical varicosities (a) to the deciduous and amniotic placenta (b) on a sagittal image. Results: Among 202 patients, 14 (6.9%) patients were pathologically diagnosed as having placenta accreta spectrum. Further, 38 (18.8%) patients had anterior placenta previa and 164 (81.2%) patients had posterior placenta previa. When anterior placenta previa with placenta accreta spectrum was predicted using at least one of the four MRI findings, the sensitivity and specificity of the anterior placenta previa with placenta accreta spectrum were 87.5% and 86.7%, respectively. In contrast, the sensitivity and specificity of posterior placenta previa with placenta accreta spectrum were 42.9% and 96.2%, respectively. But when the A/B ratio was set at 0.20, the sensitivity and specificity of the prediction for posterior placenta previa with placenta accreta spectrum using cervical varicosities were 100.0% and 89.2%, respectively. Conclusions: The findings of MRI to predict the anterior placenta previa with placenta accreta spectrum were different from posterior placenta previa. The cervical varicosities may be useful in predicting posterior placenta previa with placenta accreta spectrum.